Analysis of Factors Affecting Bond Ratings on Companies Listed on the Indonesia Stock Exchange - Damanik, Imam Rohtuah; Erlina, Erlina; Abubakar, Erwin (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This study aims to examine and analyze the factors that influence bond ratings on companies listed on the Indonesia Stock Exchange with the research period from 2018 to 2020. This study uses the variables of leverage ratio, liquidity, profitability, company size and operating cash flow. as independent variable, and audit quality variable as moderating variable. The population in this study were 55 companies listed on the Indonesia Stock Exchange and ranked by PT Pefindo during 2018 to 2020, the sample selection used a census sampling technique so that all members of the population as many as 55 companies became the research sample. The data analysis method used multiple linear regression analysis and interaction test using eviews software testing tool. The results of partial research are only the leverage ratio variable that has a positive and significant effect on bond ratings, while the variables of liquidity, profitability, firm size and cash flow from operating activities have no effect on bond ratings. Simultaneously, the variables of leverage ratio, liquidity, profitability, firm size and cash flow from operating activities have a significant effect on bond ratings. The results of the moderated regression analysis test show that the audit quality variable is significantly able to moderate the effect of the leverage variable on bond ratings, but audit quality is unable to moderate the effect of liquidity, profitability, company size and cash flow from operating activities on bond ratings of companies listed on the Indonesia Stock Exchange. and PT Pefindo for the period 2018 to 2020.